Space and Anthropology of Limit: A Philosophical Perspective - Pirni, Alberto (Frontiers in Astronomy and Space Sciences, 2016)
In no other living species does technology (or more precisely the need for technological development) play such an important role as it does in the human species. This rationale remains surely a matter of fact regarding the “traditional” or “common” condition of the man, understood as a being living “on the Earth” and with a specific and consolidated biological structure. However, any possible understanding of the same issue requires new efforts if and as far we try to maintain it open in a totally different context: “the space,” namely, a not-specific place outside Earth in which the man is trying to give shape to a new path of its own surviving (§ 1). Here rises what we would like to call the “anthropology of limit.” In order to grasp a provisional content for such expression, we must proceed analytically, first, by reconsidering briefly the two conceptual sides implied in that expression, namely “What is a man?” and “What do we mean with limit?” (§ 2). Secondly, we should try to reconsider the twofold results under a synthetical or comprehensive point of view, trying to gather a common area of questioning that opens up if and as far we reconsider both conceptual sides of that expression within the “space-context” (§ 3).